A Simple and Efficient eight node Finite Element for Multilayer Sandwich Composite Plates Bending Behavior Analysis (Fracture and Structural Integrity, 2022)
In this paper, a C0 simple and efficient isoparametric eight-node displacement-model based on higher order shear deformation theory is proposed for the bending behavior study of multilayer composites sandwich plates. Difficult C1-continuity requirement is overcome by extracting the seven degrees of freedom from strain relations for each element node: two displacements for in-plane behavior and five bending unknowns namely: a transverse displacement, two rotations and two shear angles, which results in a kinematic approximation formulation having only first order derivative requirement. The governing equations of the element (constitutive, virtual work and equilibrium equations) are implemented for the prediction of approximate solutions of deflections and stresses of sandwich plates linear elastic problems. Thereby, the formulation element is able to present a cubic in-plane displacement along both core and faces sandwich thickness, as well as, the shear stresses are found to vary as quadratic field without requiring shear correction factors and independent from any transverse shear locking problems. The accuracy and validity of the proposed formulation is verified through the numerical evaluation of displacements and stresses and their comparison with the available analytical 3D elasticity solutions and other published finite element results.
Keywords: Third Order Shear Deformation Theory; Sandwich Composite Plates; Finite Element; Bending Behavior